A simulation model of gramma configuration stirling engine with non-sinusoidal motion - Ong, Yon Siang (2024)
Stirling engine is an external combustion engine that able to convert heat energy to work. The ideal Stirling engine works according to the Stirling cycle where the processes are isothermal gas compression, isochoric gas heating, isothermal gas expansion and finally isochoric gas cooling. These processes can be realised by 2 pistons that regulate the flow of gas between 2 different temperature chambers; and heat exchangers (heater, cooler and regenerator) that regulate the gas temperature in different parts of the engine. Each of the 2 pistons of the conventional Stirling engine moves in a sinusoidal/near sinusoidal pattern with a 90° phase different between them. Mechanisms that generate sinusoidal/near sinusoidal motions like slider-crank, scotch yoke, rhombic drive and etc. are robust, have smooth/ continuous motion. However, using these sinusoidal/near sinusoidal motion sacrifice thermal efficiency or work output of the engine for smooth operation. In this work, a numerical model of gamma configuration Stirling engine with non-sinusoidal piston motion was built to study the changes in engine output and its thermal efficiency when compared with conventional sinusoidal motion. Form-closed cam with oscillating follower is used as a nonsinusoidal motion generator in this study to simulate the Stirling engine performance. Ideal isothermal model/ Schmidt model will be used in the simulation to predict the engine work output and thermal efficiency. Results showed that by substituting the sinusoidal motion mechanism with a non-sinusoidal form-closed cam, the indicated work output of the engine is increased by 1.0665W in the Schmidt model simulation or 0.9627W in Urieli and Berchowitz model simulation, while the thermal efficiency has no significant change. Modified Scotch yoke mechanism that can generate different non-sinusoidal piston motion was also simulated. It shows an increase of around 26% indicated power and a decrease in thermal efficiency by less than 1% when compared to the conventional crank-slider mechanism.